(untitled) (New Delhi, 1995)
The overall focus on what is generally understood as the ‘Kashmir Problem’ and on which much discussion has taken place, overlooks the actual occupation, albeit by illegal aggression, by Pakistan of this sizeable chunk of the state of Jammu and Kashmir. This book, is one of the pioneering efforts done by Institute for Defence Studies and Analyses (IDSA), to focus on this region. The well-researched papers put together in this volume focus on various aspects of POK, its history, its problem and its present situation. It is a book which opens the doors onto a debate which pertains to the political questions of aggression, international boundaries, as well as the more social questions of ethnic boundaries and identity problems of people within a Nation State.
Keywords: Jammu and Kashmir (India),Jammu và Kashmir (Ấn Độ); Politics and government,Chính trị và chính phủ